Gamified AI Analysis as Learning Media for Islamic Education on Students’ Learning Outcomes - Margareta, Siska; Sesmiarni, Zulfani; Zakir, Supratman (Sistemasi: Jurnal Sistem Informasi, 2025)
This research investigates the effectiveness of a gamified AI learning medium, specifically the “Marbel Shalat” game, on the learning outcomes of second-grade students in Islamic Religious Education (PAI) at SDIT. Employing a quantitative research design with a One-Group Pretest-Posttest approach, the study involved a sample of 36 students of SDIT Tahfizh Daarul Huda Sariak Laweh and SDIT Al-Kautsar Bukittinggi. Data were collected through pre-tests and post-tests, alongside observations and questionnaires to assess the impact of the gamified learning medium. The pre-test results indicated that only 15 students (41.67%) achieved mastery of the material, while the post-test results revealed a significant improvement, with 33 students (91.61%) reaching mastery. Statistical analysis confirmed the reliability and validity of the assessment instruments, demonstrating a very strong positive correlation (r = 0.860) between the pre-test and post-test scores. Furthermore, a t-test indicated a statistically significant difference in learning outcomes before and after the intervention (t = 9.83). The findings suggest that the “Marbel Shalat” game effectively enhances student learning in PAI, highlighting the potential of gamified AI as a valuable educational tool for improving student engagement and understanding of complex subjects.